Rock eval analysis of sediment core PS115/2_2 - Ruediger Stein; Thomas Frederichs; Kirsten Fahl; Walter Geibert; Jens Matthiessen; Frank Niessen; Christoph Vogt; Cynthia Sassenroth; Evgenia A Bazhenova (PANGAEA, 2025)
Sediment Core PS115/2-2 was recovered from the Amundsen Basin in 3600 m water depth at the eastern flank of the Gakkel Ridge during Polarstern Expedition PS115/2 in 2018 (Stein, 2019). The well-dated core is used to reconstruct in detail the interrelationship between ice-sheet dynamics and organic carbon burial in the central Eurasian Basin during the last 430 kyr, and to correlate marine and terrestrial records of the Eurasian Ice Sheet (EIS) history. Using organic-geochemical bulk parameters (i.e., TOC, C/N ratios, Rock Eval) and biomarkers, we have identified prominent well-defined sections with strongly elevated concentration of ancient (petrogenic) predominantly terrestrial OC, coinciding with glacial time intervals of extended ice sheets and the subsequent terminations/deglacials. Rock-Eval pyrolysis was performed on bulk ground sediment samples using a Rock-Eval 6 analyzer (cf., Lafarque et al., 1998) to determine (1) the amount of hydrocarbons (HC) present (S1 peak) and generated by pyrolytic degradation of the OC during heating up to 650°C (S2 peak), (2) the amount of carbon dioxide (CO2) generated from the decomposing OC during heating up to 390 °C (S3 peak), and (3) the temperature of maximum pyrolysis yield (Tmax value in °C). The HC and CO2 yields were normalized to OC and expressed as hydrogen index (HI) in mgHC/gOC and oxygen index (OI) in mgCO2/gOC, respectively, and may give information about the composition of the organic matter. Tmax values may give further information about the composition as well as the maturity of the organic matter. For details and methods, we refer to Stein et al. (this paper).
In: Stein, R et al. (2025): A 430 kyr multi-proxy record of Eurasian Ice Sheet history and organic carbon burial in the eastern Eurasian Basin, Arctic Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.975790